Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Remaja Putri di SMA Negeri 2 Kupang Tengah - Fitri Sevrilianti Boimau; Afrona E. L Takaeb; Maselinus Laga Nur (Yayasan Literasi Sains Indonesia, 2024)
Anemia is a condition in which the number of red blood cells or hemoglobin is less than normal or the level of red blood cells/hemoglobin in the blood decreases. The prevalence rate of anemia in indonesia in 2021 in adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. The prevalence rate of anemia in female adolescents at SMA N 2 Kupang Tengah in 2022 is 43 female adolescents. Objective; this study was to determine the factors associated with the incidence of anemia in young women at SMA N 2 Kupang Tengah. The type of research used in this research is an analytic survey with a cross-sectional research design using quantitative research methods. This research began in December 2022-January 2023 at SMA N 2 Kupang Tengah, Kupang Regency. The method used in this research is random sampling. The statistical test used in this study is the Chi-Square. The results showed that the factors associated with anemia in female adolescents at SMA N 2 Kupang Tengah were knowledge level (p=0.000), income level (p=0.000), menstrual cycle (p=0.023), nutritional status (p=0.100). Bivariate analysis showed that there was a relationship between knowledge level, income level, menstrual cycle and nutritional status which had no relationship. It was concluded that the factors associated with the incidence of anemia in SMA N 2 Kupang Tengah were suggested to health workers to increase promotional efforts by conducting socialization or counseling to increase the knowledge of young women.